(untitled) (Revista Repique, 2025)
This study investigates the analysis and implementation of the Personal Learning Environment (PLE) in the teaching of Biology at the Angel Modesto Paredes Educational Unit. Within the main objective of the research, the ability to use digital tools such as Symbaloo lesson plans to generate PLE, in order to improve the academic performance of students in the subject of Biology, Natural Sciences Area, and to promote the use of ICT in the teaching-learning process was examined. Since a descriptive approach was used to determine the use of PLE with traditional teaching, to adapt to the demands of the current educational environment; it was found that the performance of students in Biology was unfavorable, which prompted the adoption of digital strategies that encourage active and personalized learning. This work aims to change current teaching methods so that teachers can use ICT to enrich teaching and respond to the needs of today’s society, providing dynamic learning that is better adapted to the individual needs of students.